Phase 1 study combining alisertib with nab-paclitaxel in patients with advanced solid malignancies. (September 2021) - Lim, Kian-Huat; Opyrchal, Mateusz; Acharya, Abhi; Boice, Nick; Wu, Ningying; Gao, Feng; Webster, Jace; Lockhart, Albert C.; Waqar, Saiama N.; Govindan, Ramaswamy; Morgensztern, Daniel; Picus, Joel; et al.
Abstract: Aim: Aurora kinase A (AURKA) is a pleiotropic serine/threonine kinase that orchestrates mitotic progression. Paclitaxel stabilises microtubules and disrupts mitotic spindle assembly. The combination of AURKA inhibitor (alisertib) plus paclitaxel may be synergistic in rapidly proliferative cancers. We evaluated the safety and maximum tolerated dose (MTD) of alisertib in combination with nab-paclitaxel and its preliminary efficacy in patients with refractory high-grade neuroendocrine tumours (NETs). Method: This is a two-part, Phase 1 study. In Part A (dose escalation), a standard 3 + 3 design was used to determine MTD. In Part B (dose expansion), patients with predominantly refractory high-grade NETs were enrolled. Results: In total, 31 patients were enrolled and treated (16 in Part A and 15 in Part B). The MTD of alisertib was 40 mg BID on D1-3 per week and nab-paclitaxel 100mg/m 2 weekly: 3 weeks, 1 week off. Dose-limiting toxicity was neutropenia, and other common side-effects included fatigue, mucositis, and diarrhoea. In Part A, a patient with small-cell lung cancer with partial response (PR) was treated for more than 2 years, whereas four other patients with pancreatic ductal adenocarcinoma (one patient), small cell lung cancer (SCLC) (two patients), or high-grade NET (one patient) achieved stable disease (SD). In Part B, 13 of 15 enrolled patients had high-grade NETs. Of these, one had PR, and four had SD for more than 10 months. Conclusions: The combination of alisertib and nab-paclitaxel has manageable side-effect profile and showed promising preliminary efficacy in high-grade NETs, warranting further testing. Trial registration: ClinicalTrials.gov identifier: NCT01677559 . Highlights: Dysregulation of Aurora kinase A drives uncontrolled proliferation in many cancers. Alisertib is an Aurora kinase A inhibitor that may synergise with chemotherapy. The dose-limiting toxicity of alisertib plus nab-paclitaxel was neutropenia. Alisertib + nab-paclitaxel showed preliminary efficacy in high-grade NETs.